2002
DOI: 10.3168/jds.s0022-0302(02)74164-7
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Identification of Commercial Probiotic Strains

Abstract: Products containing probiotic bacteria are gaining popularity, increasing the importance of their accurate speciation. Unfortunately, studies have suggested that improper labeling of probiotic species is common in com mercial products. Species identification of a bank of com mercial probiotic strains was attempted using partial 16S rDNA sequencing, carbohydrate fermentation anal ysis, and cellular fatty acid methyl ester analysis. Re sults from partial 16S rDNA sequencing indicated dis crepancies between speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 30 publications
1
77
0
4
Order By: Relevance
“…For this purpose, nucleic acid-based techniques have been used. Highly discriminative molecular methods such as 16S rRNA gene sequencing and oligonucleotide probes can also be used for accurate probiotic species labeling, which is important for responsible quality control efforts, to build consumer confidence in product labeling, and for safety considerations (Yeung et al, 2002). The reliable identification of probiotics requires molecular methods with a high taxonomic resolution that are linked to up-to-date identification libraries.…”
Section: Studies On Probiotics Quality Control In Aquaculturementioning
confidence: 99%
“…For this purpose, nucleic acid-based techniques have been used. Highly discriminative molecular methods such as 16S rRNA gene sequencing and oligonucleotide probes can also be used for accurate probiotic species labeling, which is important for responsible quality control efforts, to build consumer confidence in product labeling, and for safety considerations (Yeung et al, 2002). The reliable identification of probiotics requires molecular methods with a high taxonomic resolution that are linked to up-to-date identification libraries.…”
Section: Studies On Probiotics Quality Control In Aquaculturementioning
confidence: 99%
“…Attention to such features is important, as it has been repeatedly shown that in about 50% of the probiotic products the identity of recovered microorganisms does not correspond to the information stated on the product label (Yeung et al, 2002;Fasoli et al, 2003;Temmerman et al, 2003;Theunissen et al, 2005).…”
Section: Taxonomymentioning
confidence: 99%
“…Mislabelling may have serious safety implications. For example, mislabelling closely related species of lactobacilli maybe is not too worrying, but failure to properly identify or label the bacterial genus such as products labelling Lactobacillus acidophilus and containing Streptococcus sanguis (Yeung et al, 2002) or failure to list bacterial contents such as Enterococcus (Yeung et al, 2002) or Staphylococcus (Fasoli et al, 2003) are concerning from the point of view of safety of those products. These observations indicate the importance of rigorous quality control at every stage of the production and of each production batch.…”
Section: Taxonomymentioning
confidence: 99%
“…Probiotics are the live microbial feed supplements which beneficially affect the host by improving the microbial balance (Yeung et al, 2002). The microbes, Lactobacilli and Bifidobacteria, are gram + ve bacteria producing lactic acid and extensively studied to improve cocoon characters in B.mori L (Masthan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%